Oxidised stainless steel: a very effective electrode material for microbial fuel cell bioanodes but at high risk of corrosion. (10th March 2015) - Ledezma, Pablo; Donose, Bogdan C.; Freguia, Stefano; Keller, Jurg
Highlights: Oxidised SS bioanodes produced a maximum current density of 45.367 mA cm −3 . SS exposed to electroactive bacteria is continuously ennobled even after 65 days. Exposure to these bacteria also reduces SS passivation, increasing corrosion risk. Ennoblement & loss of passivation are apparently not related to bacterial attachment. Abstract: Bioelectrochemical systems (BES) are gaining momentum as biotechnological alternatives for self-powered wastewater treatment and the recovery of valuable products from waste. However, there is a strong need to reduce system costs and therefore some types of stainless steel (SS) electrodes have been proposed as an alternative to carbonaceous electrode materials, but their corrosion remains a strong concern. We hereby demonstrate that a facile SS modification results in up to 45.367 mA cm −3 current production at room temperature – the highest volumetric current density reported to date for BES bioanodes–but that this benefit comes at a high risk of corrosion, which compromises the applicability of SS-based Microbial Fuel Cells.